Exploring Awareness of Medical Textiles in Healthcare Products Among Young Women (International Journal of Food and Nutritional Sciences, 2022)
Medical textiles have become an essential part of contemporary healthcare, providing creative answers to a range of medical problems. This essay delves into the complex realm of medical textiles, examining its key traits, many uses, and prospective effects on healthcare. Medical textiles are appropriate for use in medical applications when they have certain properties, including biocompatibility, porosity, breathability, absorbency, and sterility. They are used in orthopaedics, surgery, wound care, implants, and hygiene products, and they significantly improve patient comfort and treatment outcomes. Their potential is further increased by the incorporation of smart fabrics and nanotechnology, allowing for improved functionality and real-time monitoring. Medical textiles continue to progress healthcare as researchers and professionals work together, promising a future where patient care is further optimised through the invention of these materials